Boundedness of Global Solutions for a Heat Equation with Exponential Gradient Source - Zhengce Zhang; Yanyan Li (Abstract and Applied Analysis)
We consider a one-dimensional semilinear parabolic equation with exponential gradient source and provide a complete classification of large time behavior of the classical solutions: either the space derivative of the solution blows up in finite time with the solution itself remaining bounded or the solution is global and converges in C1 norm to the unique steady state. The main difficulty is to prove C1 boundedness of all global solutions. To do so, we explicitly compute a nontrivial Lyapunov's functional by carrying out the method of Zelenyak.